RGD-conjugated mesoporous silica-encapsulated gold nanorods enhance the sensitization of triple-negative breast cancer to megavoltage radiation therapy - Zhao N (Dove Medical Press, 2016)
Ning Zhao,1,2,* Zhangru Yang,2,3,* Bingxin Li,2 Jin Meng,2 Zeliang Shi,2 Ping Li,4 Shen Fu4 1Department of Radiation Oncology, Fudan University Shanghai Cancer Center, Shanghai, People’s Republic of China; 2Department of Radiation Oncology, 6th People’s Hospital of Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 3Med-X Research Institute and School of Biomedical Engineering, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 4Department of Radiation Oncology, Shanghai Proton and Heavy Ion Center, Fudan University Shanghai Cancer Center, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: Multifunctional nanoprobes have great potential as effective radiosensitizers and drug carriers. RGD-modified gold nanorods could increase the uptake of nanoparticles via receptor-mediated endocytosis in integrin alphaV beta3-overexpressing breast cancer cells, which could enhance the effects of radiation on tumor cells, leading to further radiosensitization. The purpose of our study was to demonstrate that RGD-conjugated mesoporous silica-encapsulated gold nanorods significantly enhanced the sensitization of triple-negative breast cancer to megavoltage energy. The results indicated that RGD-conjugated mesoporous silica-encapsulated gold nanorod multifunctional nanoprobes could achieve radiosensitization in vitro and in vivo, which suggests the potential translation of this nanotechnology to clinical applications in tumor-targeting and selective therapy. Keywords: gold nanorods, triple-negative breast cancer, Arg-Gly-Asp peptides, integrin alphaV beta3, megavoltage radiation therapy